2015
DOI: 10.1002/jobm.201500195
|View full text |Cite
|
Sign up to set email alerts
|

Specific rhizobacterial resources: characterization and comparative analysis from contrasting coastal environments of Korea

Abstract: This study analyzed the rhizobacterial distribution from two coasts, which show contrasting climates and geographical and geological characteristics, to secure specific microbial resources. Furthermore, rhizobacteria were characterized and the results were comparatively analyzed with reference to the characteristics of two coastal environments. For this purpose, three representative halophyte species communities native to the Dokdo Islands and the East Sea coast of Korea were selected. Partial identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
2
8
0
1
Order By: Relevance
“…Understanding the role of PGPR in functional growth promotion, particularly in terms of PGP activities, such as plant growth and yield enhancement requires continuous efforts to identify and characterize new PGPR under field conditions (Khan et al, 2009a ). However, plant-microbe interactions are very complex and can be highly variable due to variations in ecological conditions, soil physicochemical properties, host responses, and bacterial fitness and adaptation mechanisms (You et al, 2016 ; Zhou et al, 2016 ; Eida et al, 2017 ). Soussi et al ( 2016 ) reported that the selection and recruitment of bacteria by plants is dependent on bio-pedo-agroclimatic factors in addition to the plant genotype, and that their diversity and functional redundancy plays an important role in supporting the plant's health and development under abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the role of PGPR in functional growth promotion, particularly in terms of PGP activities, such as plant growth and yield enhancement requires continuous efforts to identify and characterize new PGPR under field conditions (Khan et al, 2009a ). However, plant-microbe interactions are very complex and can be highly variable due to variations in ecological conditions, soil physicochemical properties, host responses, and bacterial fitness and adaptation mechanisms (You et al, 2016 ; Zhou et al, 2016 ; Eida et al, 2017 ). Soussi et al ( 2016 ) reported that the selection and recruitment of bacteria by plants is dependent on bio-pedo-agroclimatic factors in addition to the plant genotype, and that their diversity and functional redundancy plays an important role in supporting the plant's health and development under abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Halophytes require salt for survival. Therefore, comparatively higher concentrations of Na + might be absorbed by halophytes native to the Dokdo Islands than the concentrations absorbed by those on the East Sea or West Sea coasts [ 29 ]. This might be caused by the drastic seawater intrusion and accumulation of salt on the coast of the Dokdo Islands [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, isolates from L. mauritiana and A. spathulifolius , which are native to the West Sea, only grew at pH 4.0–7.0. Considering that the pH of seawater is approximately 8.3 [ 30 ], the large seawater intrusions or low soil buffering capacity of the Dokdo Islands might lead to Na + accumulation in the halophytes' internal tissue [ 20 29 31 ]. Thus, the high proportion of alkalophilic fungal endophytes might have resulted from adaptation to this specialized plantenvironment interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, a virgin terrain on Ulleung Island that represents the inland geography with very limited human access was selected. Accordingly, the RP and RS samples of the Korean bellflower were collected from 3 geographically segregated sites: (1) the Dokdo Islands (Seodo), a rocky oceanic island with volcanic origin [7,18,19]; (2) the coastline of Ulleungdo Island, which has less harsh conditions than those of Seodo [19]; (3) the central inland area of Ulleungdo Island, which is surrounded by mountain ranges composed of virgin primeval forests ( Figure 1 and Table 1) [19,20]. All these areas have been designated as National Reserve by the Cultural Heritage Administration of Korea (CHA) for the purpose of conservation [7].…”
Section: Methodsmentioning
confidence: 99%